Q.2 If p = -2, find the value of:
(i) 4p + 7
\((ii) -3p^2 + 4p + 7\)
\((iii) -2p^3 – 3p^2 + 4p + 7 \)


Answer :

(i) 4p + 7
= (4 × (-2)) + 7
= -8 + 7
= -1
\((ii) -3p^2 + 4p + 7\)
\(= (-3 × (-2)^2) + (4 × (-2)) + 7\)
= (-3 × 4) + (-8) + 7
= -12 – 8 + 7
= -20 + 7
= -13
\((iii) -2p^3 – 3p^2 + 4p + 7 \)
\(= (-2 × (-2)^3) – (3 × (-2)^2) + (4 × (-2)) + 7 \)
= (-2 × -8) – (3 × 4) + (-8) + 7
= 16 – 12 – 8 + 7
= 23 – 20
= 3

NCERT solutions of related questions for Algebraic Expressions

NCERT solutions of related chapters class 7 maths

NCERT solutions of related chapters class 7 science